Private schooling and gender justice: An empirical snapshot from Rajasthan, India's largest state. (January 2016) - Kelly, Orla; Krishna, Aditi; Bhabha, Jacqueline
Highlights: We compare attributes and experiences 413 young women, from economically and educationally disadvantaged backgrounds who attended government versus private schools at the primary and secondary level. We found Caste more than income or years of parental education was the biggest predictor of school type attended Private schools had better infrastructural provisions, higher rates of reported peer bullying and better 10 th standard exam outcomes. Those who attended low fee private schools reported substantially elevated educational costs compared to government schools Paradoxically, a larger portion of participants who attended government schools reported their families had fallen into debt to support their education. Reports of teacher violence and teacher absenteeism were largely consistent across institution types. Those whose parents had the lowest rates of educational attainment were the most likely to report having been victimized. Abstract: In this paper, we compare the key attributes and experiences of a sample of 413 young women, who attended government versus private schools at the primary and secondary level. Study participation was limited to those whose parents had completed only upper primary education or less. At the time of the study, participants were in their second year of undergraduate study in government colleges across Rajasthan, the largest state in India. We found, among this socially narrow sample, that caste more than income or years of parental education was the biggest predictor of school type attended at the primary and secondary level. We found other significant differences. Private schools had better infrastructural provisions (including girls' toilets), marginally higher rates of reported peer bullying and better 10th standard exam outcomes. Those who attended private schools reported substantially elevated educational costs (direct fees but also disqualification from government schemes). Paradoxically, a larger portion of participants who attended government schools reported their families had fallen into debt to support their education. These finding support the theory that the most disadvantaged continue to rely on a public education system that yields poor exam results. Reports of teacher violence and teacher absenteeism were largely consistent across institution types. While overall rates of teacher violence were low, those whose parents had the lowest rates of educational attainment were the most likely to report having been victimized in both government and private schools. We explore the implications of these findings for the achievement of gender equality at the post-primary level.